Vulnerability assessment and analysis of cryosphere changes in the Western Sichuan Plateau - Lumin Nie; Zihan Zhang; Heng Lu (Arctic, Antarctic, and Alpine Research)
A vulnerability assessment model and indicator system for the changes in the cryosphere in the Western Sichuan Plateau are constructed based on the “exposure–sensitivity–adaptive capacity” framework. The model aims to capture the multiple characteristics of vulnerability to cryosphere changes in the region by selecting influencing factors from three dimensions: exposure, sensitivity, and adaptive capacity. Furthermore, the study explores the interrelationships among vulnerability dimensions and employs geographical detectors to analyze the driving mechanisms of vulnerability. The ultimate goal is to provide a scientific and rational basis for developing effective adaptation strategies to prevent and mitigate cryosphere-related disasters in the area. The main findings are as follows: (1) The vulnerability to cryosphere changes in the Western Sichuan Plateau exhibits a distribution pattern characterized by higher vulnerability in the west and lower vulnerability in the east. (2) There is a significant correlation between vulnerability and geographical location, characterized by two types of distribution patterns: high–high aggregation and low–low aggregation. The aggregation patterns are relatively stable but exhibit spatial heterogeneity. (3) The vulnerability to cryosphere changes in the Western Sichuan Plateau is the combined result of natural geographical conditions, socioeconomic development levels, and other factors.